Drug Utilization Pattern using World Health Organization prescribing Indicators at Otorhinolaryngology OPD of a tertiary teaching hospital of Eastern Nepal - Sah, Bajarang Prasad; Paudel, Deepak; Sarraf, Deependra Prasad (Birat Journal of Health Sciences, 2020)
Introduction: Assessment of drug utilization pattern using the World Health Organization (WHO) prescribing indicators is important to promote rational drug therapy.It needs to be evaluated periodically to obtain information about drug utilization pattern, to detect early signals of irrational use of drugs and to provide feedback to prescribers. Objective: The objective of the present study was to assess the drug prescribing patterns in the Otorhinolaryngology OPD based on the WHO prescribing indicators. Methodology: A cross-sectional study was conducted among 148 outpatients at Otorhinolaryngology and HNS department of B.P. Koirala Institute of Health Sciences for six month duration. Patients aged 18 years and above and prescribed at least one drug were enrolled. Medical case sheets of the every fifth patients visiting the OPD were reviewed to collect the relevant data on a self-designed proforma. Descriptive statistics and WHO prescribing indicators were calculated using SPSS version 11.0. The study was approved by Institutional Review Committee, B.P. Koirala Institute of Health Sciences Results: A total of 322 drugs were prescribed to 148 patients. Most of the drugs were prescribe through oral route (69.3%). Levocetrizine (10.6%) was the commonest prescribed drug followed by Ibuprofen+Paracetamol (10.2%) and Pantoprazole (10.2%). Among systemic antibiotics, Amoxicillin+Clavulanic acid (35.9%) was the most frequently prescribed followed by Cefixime (12.8%) and Levofloxacin (12.8%). Ofloxacin + Dexamethasone (22.9%) was the most frequently prescribed topical drug followed by Mometasone (17.7%). The average number of drugs prescribed per encounter or mean was 2.2 (range 1-5). The percentage of encounters in which an antibiotic was prescribed was 33.2%. The percentage of drugs prescribed by generic name and from National List of Essential Medicine (NLEM) was 28% and 31.9% respectively. Conclusions: The drug utilization pattern did not comply with the most of the WHO prescribing indicators. The average number of drug per prescription was higher than recommended by WHO, generic prescribing was remarkably lower and prescribing from NLEM was also low.